Allergic contact versus irritant contact dermatitis in patients with hard-to-heal leg ulcer: clinical and diagnostic approach. (2nd May 2021) - Monari, Paola; Fusano, Marta; Moro, Ruggero; Baiguini, Ilaria; Calzavara-Pinton, PierGiacomo; Vascellaro, Annalisa; Gualdi, Giulio
Abstract : Background: Dermatitis of surrounding skin may complicate hard-to-heal leg ulcers, delaying wound healing. The coexistence of hard-to-heal leg ulcers and irritant or allergic contact dermatitis may create difficulties for both diagnostic and therapeutic management. Objective: The aim of our study was to evaluate the incidence of dermatitis occurring in the surrounding skin in a population affected by hard-to-heal leg ulcers during treatment, and to differentiate between allergic contact dermatitis (ACD) and irritant contact dermatitis (ICD) with the use of a patch test. Furthermore, we investigated which medications were most probably related to these conditions. Method: We conducted an observational study from 21 February to 21 July 2017, enlisting all patients affected by hard-to-heal leg ulcers who attended the Wound Care Service of the Dermatologic Department of ASST, Spedali Civili, Brescia, Italy. Results: We enrolled 95 patients; 81 patients did not develop dermatitis, while 14 patients developed dermatitis of the surrounding skin. These patients underwent a patch test which gave a positive result in seven patients, permitting the diagnosis of ACD. Conclusion: Our study confirmed the incidence of dermatitis of the surrounding skin reported in the literature but reassessed the incidence of ACD as opposed to ICD.